Curcumin: Synthesis optimization and in silico interaction with cyclin dependent kinase - Ahmed Mahmood; Abdul Qadir Muhammad; Imtiaz Shafiq Muhammad; Muddassar Muhammad; Hameed Abdul; Nadeem Arshad Muhammad; Asiri Abdullah M. (Acta Pharmaceutica)
Curcumin is a natural product with enormous biological potential. In this study, curcumin synthesis was revisited using different reaction solvents, a catalyst (n-butylamine) and a water scavenger [(n-BuO)3B], to develop the optimal procedure for its rapid acquisition. During synthesis, solvent choice was found to be an important parameter for better curcumin yield and high purity. In a typical reaction, acetyl acetone was treated with boron trioxide, followed by condensation with vanillin in the presence of tri-n-butyl borate as water scavenger and n-butylamine as catalyst at 80 °C in ethyl acetate to afford curcumin. Moreover, curcumin was also extracted from turmeric powder and spectroscopic properties such as IR, MS, 1H NMR and 13C NMR with synthetic curcumin were established to identify any impurity. The purity of synthetic and extracted curcumin was also checked by TLC and HPLC-DAD. To computationally assess its therapeutic potential against cyclin dependent kinases (CDKs), curcumin was docked in different isoforms of CDKs. It was observed that it did not dock at the active sites of CDK2 and CDK6. However, it could enter into weak interactions with CDK4 protein.